Pengaruh Pendidikan Islam Dalam Keluarga Dan Budaya Religius Sekolah Terhadap Kecerdasan Spiritual Siswa di MIN 3 Ponorogo - Anitasari, Lia; Murdianto, Murdianto; Fikriawan, Suad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of the study was to determine the influence of Islamic education in the family and religious culture of the school on the spiritual intelligence of students at MIN 3 Ponorogo. This study was conducted at MIN 3 Ponorogo using quantitative research methods and the research design was correlation research. The population in this study were 217 students in grades 4-6. The sampling technique was random sampling. The researcher took a sample of 54 people as respondents. Data analysis used multiple regression analysis, t-test, F-test with a quantitative approach. The results of the study concluded that Islamic education in the family and religious culture of the school had a very strong influence, both partially and simultaneously on the spiritual intelligence of students at MIN 3 Ponorogo. While the simultaneous contribution or contribution of the variables of Islamic education in the family and religious culture of the school to the spiritual intelligence of students at MIN 3 Ponorogo was 99% and 1% was influenced by other variables.